The critically endangered flapper skate (Dipturus intermedius): Recommendations from the first flapper skate working group meeting. (February 2021) - Garbett, Amy; Phillips, Natasha D.; Houghton, Jonathan D.R.; Prodöhl, Paulo; Thorburn, James; Loca, Sophie L.; Eagling, Lawrence E.; Hannon, Gary; Wise, Daniel; Pothanikat, Liz; Gordon, Cat; Clarke, Maurice; et al.
Abstract: The flapper skate, Dipturus intermedius (Parnell, 1837), is the largest of all European skate and rays (Superorder: Batoidea). It is found in coastal waters of the European continental shelf and slopes in the North-East (NE) Atlantic. With the 2006 IUCN Red List of Threatened Species classification of 'common skate' as Critically Endangered, and the recognition in 2010 that this name masked two species (flapper skate and blue skate D. batis (Linnaeus, 1758)), and to better support conservation on this regional scale, the Flapper Skate Working Group (SWG) was formed. The SWG is a consortium of government, NGOs, sport-fishing associates and academics, including participants from the UK, Ireland and the Netherlands. The purpose of the SWG is to consolidate relevant research, advocacy and policy expertize for the purpose of flapper skate conservation. The first SWG workshop took place in Belfast, November 2019, with discussions focussed on conservation in the NE Atlantic. Following two days of talks, workshops and discussions, we present the SWG's key recommendations for future collaborative conservation.